2015
DOI: 10.1111/1365-2745.12362
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous pulsed flowering in a temperate legume: causes and consequences of multimodality in the shape of floral display schedules

Abstract: Summary1. In plants, the temporal pattern of floral displays, or display schedules, delimits an individual's mating opportunities. Thus, variation in the shape of display schedules can affect the degree of population synchrony and the strength of phenological assortative mating by flowering onset date. A good understanding of the mechanisms regulating the timing of flowering onset has been developed, but we know less about factors influencing subsequent patterns of floral display. 2.We observed unusual multimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…), and phenological traits (Kelly ; Wadgymar et al. ,b; Wadgymar and Weis ), making it an ideal system for studying capacity for adaptation and G × E . In the fall of 2013, seed pods from 200 maternal plants were collected from a population of C .…”
Section: Methodsmentioning
confidence: 99%
“…), and phenological traits (Kelly ; Wadgymar et al. ,b; Wadgymar and Weis ), making it an ideal system for studying capacity for adaptation and G × E . In the fall of 2013, seed pods from 200 maternal plants were collected from a population of C .…”
Section: Methodsmentioning
confidence: 99%
“…In this experiment and in others, flowering onset for the NC population planted at KSR always occurred after August 28th, when the photoperiod in southern Ontario was 13.75 h, which is similar to the that experienced upon flowering at the NC home site on August 7th (data not shown). This occurred despite warming‐induced advances in phenology (this experiment) and even when planting seeds 2 months ahead of the MN population (Wadgymar et al ., ). This suggests that flowering onset date in C. fasciculata is under at least partial photoperiodic control and that the evolution of genes associated with photoperiodic responses would be necessary for successful long‐term establishment of populations relocated to northern latitudes.…”
Section: Discussionmentioning
confidence: 97%
“…We estimated the potential for gene flow between populations, as would occur under an assisted gene flow scenario, by analyzing the overlap in flowering schedules to determine the proportion of opportunities for pollen exchange between populations. For the few days with missing flower count data, we used a linear function running from the day before to the day after the missed count to interpolate the expected number of flowers (Wadgymar et al, 2015). Within a treatment, and for each population pairing, we used daily flower counts to construct and n 9 n matrix of pair-wise mating opportunities between all individuals.…”
Section: Temporal Reproductive Isolationmentioning
confidence: 99%
“…Several recent studies found temporal structure at neutral loci in natural populations where individual flowering periods are short relative to the flowering season length (Daïnou et al, 2012; Suni and Whiteley, 2015). In contrast, the overlap among individual flowering schedules in most temperate species is too broad to divide populations into multiple mating pools (Rabinowitz et al, 1981; Herrera, 1986; Ison et al, 2014; Weis et al, 2014; Wadgymar et al, 2015). Yet we found that the realized temporal structure was at least as strong, and potentially stronger, than the predicted structure based solely on flowering schedules (Tables 1, 2).…”
Section: Discussionmentioning
confidence: 99%